Speech Acts as a Communicative Strategy in Arabic Language Teaching - Muzakki Abdurrahman; Mahjatin Nabilah Syarofina; Nur Aqilah Lutfiya Rahma Opier (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2026)
Arabic language learning requires effective communication between teachers and students to support classroom interaction. Differences in linguistic background and communicative competence may influence how messages are delivered and understood during learning activities. Therefore, tadāwul af‘āl al-kalām (exchange of speech acts) becomes important in creating meaningful classroom communication. Speech acts also function as communicative tools that help teachers manage instruction and assist students in responding appropriately during classroom interaction. Through effective speech acts, the learning process can become more active, interactive, and learner-centered. This study aims to examine the forms, functions, and meanings of speech acts in Arabic classroom interaction and their role as communicative strategies in learning activities. This research employed a qualitative method using a pragmatic discourse analysis approach. Data were collected through classroom observation, interviews, and documentation at grade 10 of MAN 2 Gresik. The analysis focused on speech act dimensions, including locutionary, illocutionary, and perlocutionary acts, as well as speech act categories consisting of directive, assertive, expressive, commissive, and declarative forms. The findings show that teachers predominantly used directive speech acts to organize classroom activities and encourage participation. Students commonly employed assertive speech acts to express understanding and provide responses, while expressive and commissive speech acts appeared in emotional and participatory contexts. These findings indicate that speech acts contribute to classroom interaction by supporting communication, participation, and learner engagement. The use of speech acts in Arabic language learning may help create a more interactive and communicative learning environment.